Is there a spirit of overseas Chinese capitalism? - Chuah, Swee Hoon; Hoffmann, Robert; Ramasamy, B.; Tan, Jonathan H.W. (Springer, 2016)
The economic miracle of the Chinese Diaspora in Southeast Asia has been attributed to their unique economic culture forged from Confucian thought and the emigration experience. However, this Spirit of Overseas Chinese Capitalism (SOCC) hypothesis, based largely on qualitative research, has not been validated through quantitative work. This paper provides, for the first time, empirical evidence from a values survey and experiment which show that only some of the hypothesised SOCC values and behaviours differentiate the Chinese from less economically successful ethnic groups in Malaysia. While we find no evidence that Confucian values explain the success of the Overseas Chinese we do find it may lie in their (a) more conductive work values and (b) greater intra-ethnic cooperativeness, both accentuated by the emigration experience.